Exploring the perspectives of undergraduates, graduates and managers on the skills learned in higher education engineering - Lucas Trajano de Freitas Almeida; Marcele Elisa Fontana (Exacta, 2025)
The current job market has increasingly required behavioral skills from engineering professionals when compared to technical skills. However, Higher Education Institutions often do not prepare undergraduates for the real job market requirements. This study set out to analyze the gap between the skills developed during higher education (HE) in engineering from the students' perspectives (undergraduates and graduates) and those required by the labor market. Two self-administration questionnaires were developed and applied to: (1) students and former students of the engineering course, and (2) companies’ managers from the same location as the course. The data were analyzed in order to answer six hypotheses research developed based on the concepts found in the literature. The results confirm there is a gap between the skills developed by the university and the skills valued by companies. This work contributes to the discussion about the quality of HE in Engineering, mainly in developing countries like Brazil.